Epidemiologic, sorologic and molecular studies of rabies virus isolated in bat colonies of Histiotus velatus, Brazil - Martorelli, L. F. A.; Kataoka, A. P. A. G.; Campos, A. C. A.; Sobre, M. M.; Araujo, D. B.; Rosa, A. R.; Trezza Netto, J.; Oliveira, R. N.; Almeida, M. F.; Sacramento, D. V. R.; Durigon, E. L.; Favoretto, S. R. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Rabies was detected in two bats colonies of insectivorous Histiotus velatus that used as shelter ceilings of buildings in the same park in the North region of São Paulo City, Brazil in 2001 and 2009. This park although located in an urban area, has a large area of rainforest. Rabies diagnosis was made by FAT (Fluorescent Antibody Test) and MIT (Mouse Inoculation Test) techniques. The number of bats submitted to rabies diagnosis was forty-three in the first colony and forty in the second. Before it, bats received anesthesic and blood samples were collected by cardiac puncture in sixty animals (thirty-eight of the first colony and twenty-two of the second colony) and the presence of rabies virus neutralizing antibodies was determined by SFIMT (Simplified Fluorescent Inhibition Microtest). The antigenic characterization of the isolates was made using a panel of monoclonal antibodies, which was produced and provided by Centers for Disease Control and Prevention (Atlanta, U.S.A), as established by Pan- American Health Organization for characterization of rabies isolates in Americas. Five bats were positive to rabies by FAT and MIT in each colony, 12% in the first colony and 12.5% in the second. However, two bats dead of the second colony were unsuitable for rabies diagnosis by traditional techniques and their brains were submitted to RTPCR with positive results, totalizing seven positives bats indicating 23.3% of rabies virus positivity. All blood samples analyzed presented neutralizing antibodies titers and sixteen animals (40%) from the first colony and two (4.6%) of the second presented titers ≥0.5 UI/mL. There was a positive correlation between the incubation period in mice and the antibodies titers observed in the bats. The samples with the higher incubation period for MIT (29 days) were from bats that showed the highest neutralizing antibody titer. Some bats negative by MIT and FAT and apparently healthy, presented high antibodies titers. The antigenic characterization showed only one antigenic profile (positive just to MAb C12) observed in previous studies with samples isolated in the same species of bats in Brazil. Genetic characterization was performed by sequencing of a fragment of N protein region and the rabies genetic lineage identified in these study were segregated with isolates obtained from other Histiotus velatus samples isolated in other regions of Brazil. These results show the importance of these methodologies for the epidemiological surveillance of rabies virus in bats and the necessity of the monitoring of bat colonies in parks and environmental reserves frequented by humans and where living other wildlife species as preventive actions of rabies control.